The Modern Mulatto: A Comparative Analysis of the Social and Legal Positions of Mulattoes in the Antebellum South and the Intersex in Contemporary America - George, Marie-Amélie (Columbia Journal of Gender and Law, 2006)
“This case involves the most basic of questions. When is a man a man, and when is a woman a woman? Every schoolchild, even of tender years, is confident he or she can tell the difference, especially if the person is wearing no clothes.”‘ With this opening statement, Judge Harberger, writing the majority opinion in Littleton v. Prange, quickly goes on to demonstrate that this most basic of questions can be more difficult to answer than appears at first glance. The case at issue, which required the court to determine the legal sex of a post-operative transsexual, questioned the basic notion that male and female are fixed, immutable, and oppositional categories. The very premise of the case is an assault on the foundational assumption that sex is a binary and biological phenomenon, which has been overwhelming accepted in contemporary thought. Importantly, these two concepts once underpinned race theory, but were subsequently rejected by both the academic and legal worlds. The same, while examined and critiqued at length in feminist and sexuality theory, has thus far failed to occur in the realm of legal doctrine and social consciousness. This Article seeks to add to the scholarship that illustrates the way in which sex can be conceptualized in much the same way as race, and may thus be divested of the presumptions of dichotomy and physiology, by comparing the regulation of race in the antebellum period and sex in the modem day. In doing so, it also aims to undermine objections that sex and race are not in fact parallel socio-physiological categories. Specifically, this Article examines the manner in which antebellum mulattoes, whose mixed race challenged the bases for racial hierarchy, were socially and legally made black so as to be folded within the binary on which slavery depended. It then follows this analysis with a consideration of the ways in which the intersex, who are persons with ambiguously sexed genitals, chromosomes, or phenotypes, are physically forced into one sex or the other so as not to cast doubt on the sexual binary necessary to sustain a patriarchal political and social system. Using this comparison as a framework from which to extend its deconstruction of social categories, this Article then turns to an examination of the role of the law in regulating sexual identity, noting how the law has the potential to be used to create sex in much the same way as it was employed to craft race during the antebellum period.